Exploring Some Pragmatic and Stylistic Aspects in Three English Translations of Sūrah Al Hujurat: An Analytical Linguistic Study - Ali Albashir Mohammed Alhaj (International Journal of Social Sciences & Educational Studies, 2020)
The study intends to examine prudently some pragmatic and stylistic aspects in three English renditions of the meaning of Sūrah Al Hujurat, which is in the renditions of Abdel- Hakeem, Pickthall, and Khan and Al-Hilai. Also, the study aims at looking into a pragmatic and stylistic approach as a basic conceptional structure against which the three translations of the meaning of Surah Al Hujurat have been analyzed and assessed by the two researchers. Additionally, the paper aims at probing translation methods adopted by the three translators in rendering Sūrah Al Hujurat into English. The study reveals that the translation methods used by the three translators such as literal translation and transliteration have not been acknowledged and recognized as they do not convey some accurate meanings of the original text. The archaic lexemes used by Pickhall cause underlying linguistic problems for TL receptor. Contemporary usage results in pragmatic and stylistic aspects of simplicity. The modern usage has preferably been used by the three translators, especially for some young receptors of the Holy Quran. Also, the paper findings show that loss in the pragmatic and stylistic aspects of Surah Al Hujurat into English took place because of couplet translation, transliterations, literal translation methods adopted by the aforementioned three translators. The study suggests that the loss of sense in the renditions of the Holy Quran in general and Surah Al Hujurat, in particular, can be recompensed by exegeses, as well as some translation strategies such as translation in brackets or footnotes. Finally, the study recommends the translators of the Holy Quran should avoid employing transliteration and literal translation strategies in rendering the Holy Quran into English.